PRICING STRATEGIES FOR NEW AGRICULTURAL PRODUCTS - Ademi, Vjosa Fejza; Avdullahi, Ajtene (Emirates Journal of Food and Agriculture, 2021)
Pricing strategies differ for each stage of the product life cycle. Although each stage of product life has its own peculiarities and challenges, the most difficult and challenging stage is setting prices for new products. Therefore, this was the reason which aroused our curiosity to do a research which is based on the theoretical and practical plane on this issue. Initially, the literature of various authors who have contributed in the field of pricing policy for products and services in general was reviewed. Based on this analysis, a very good foundation has been laid to understand the role and importance of pricing for new products, and the most used pricing strategies for this category of products have described and analyzed. From the theoretical analysis, conclusions have been drawn which have served as a supporting basis of the practical part of the paper. To make this research more thorough, we reviewed a special case study of the local manufacturing company Pestova l.l.c, which managed to launch several new products in the market of Kosovo and the Region. In this case study, the pricing strategies that this company has selected for the products launched in the market were analyzed. Finally, the conclusions that have emerged as a result of the analysis and the literature review and the concrete data obtained from the case study for the company Pestova are provided.